PRAGMATIC POWER OR PERIL? INDONESIAN STUDENTS RESPOND TO CHATGPT'S LINGUISTIC SUBTLETIES IN ARGUMENTATIVE WRITING - Nurjamin, Lucky; Maulana, Risal; Nurjamin, Asep; Subki, Ahmad; Damayanti, Hemalia (English Review: Journal of English Education, 2025)
This study investigates Indonesian university students' responses to the pragmatic meaning conveyed by ChatGPT in the context of argumentative writing. Employing a qualitative approach, the research explores students' perceptions of the ease of understanding and utilizing the pragmatic cues embedded in AI-generated text, their attitudes toward using the tool, and their behavioral intention for continued use. Findings reveal that while students appreciate ChatGPT's usefulness and ease of use for generating argumentative content, their engagement with its pragmatic meaning is more nuanced. Students often modify AI-generated language to align with their own writing styles and perceived academic appropriateness, indicating a level of critical awareness. A writer's stance and attitude towards the argument are often conveyed through pragmatic choices. Students' modifications could reflect an effort to inject their own voice and perspective, which might be absent or inadequately represented in the AI-generated text.